2017
DOI: 10.5582/irdr.2017.01071
|View full text |Cite
|
Sign up to set email alerts
|

Expanded dengue syndrome in secondary dengue infection: A case of biopsy proven rhabdomyolysis induced acute kidney injury with intracranial and intraorbital bleeds

Abstract: Dengue fever is endemic in the Indian subcontinent and can have myriad presentations. The term expanded dengue syndrome (EDS) is used for atypical manifestations in dengue fever. We present a rare case of EDS in a patient with secondary dengue infection who developed rhabdomyolysis induced acute kidney injury (RAKI) along with intracranial and intraorbital bleeds. Patient was successfully managed in our institute and was discharged in stable condition. To the best of our knowledge, this is the only reported ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
17
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 16 publications
3
17
0
2
Order By: Relevance
“…5 There has been increasing atypical and rare presentations of DF resulting in the expanded dengue definition. 28 , 29 Some studies similar to ours from other parts of the country have reported significant differences in the incidence of atypical presentation like neurological signs or the incidence of serositis 11 , 12 while others have reported similar findings. 23 These differences may be due to co-infection with other pathogens 28 or secondary heterotypic dengue virus infections.…”
Section: Discussionsupporting
confidence: 65%
“…5 There has been increasing atypical and rare presentations of DF resulting in the expanded dengue definition. 28 , 29 Some studies similar to ours from other parts of the country have reported significant differences in the incidence of atypical presentation like neurological signs or the incidence of serositis 11 , 12 while others have reported similar findings. 23 These differences may be due to co-infection with other pathogens 28 or secondary heterotypic dengue virus infections.…”
Section: Discussionsupporting
confidence: 65%
“…The term “expanded dengue” was thus frequently used by the informants. A change in disease pattern has indeed been documented elsewhere, 27 , 28 and it has been found that dengue comes with a wider spectrum of symptoms than previously observed. 29 31 …”
Section: Discussionsupporting
confidence: 55%
“…The term "expanded dengue" was thus frequently used by the informants. A change in disease pattern has indeed been documented elsewhere, 27,28 and it has been found that dengue comes with a wider spectrum of symptoms than previously observed. [29][30][31] To overcome the diagnostic challenges mentioned, a solid system must be in place, which gives the clinicians the best possible prerequisites for making the correct diagnosis and, thus, the health authorities a correct picture of the disease burden.…”
Section: Discussionsupporting
confidence: 54%
“…Since urea is reabsorbed by the kidney, its altered levels in the blood may indicate renal dysfunction. Increased levels of BUN are often reported is renal involvement during DENV infections [ 22 , 34 , 37 , 76 , 77 ], and can be a consequence of glomerular injury or hypotension [ 37 ]. Mice blood samples were collected at 24, 48 and 72 hpi, and BUN levels were measured.…”
Section: Discussionmentioning
confidence: 99%
“…Glomerular changes affecting the kidney are often reported in dengue human cases [ 31 , 34 , 43 ] and, DENV inducing glomerulopathies is well documented [ 34 , 67 , 77 , 78 ]. Deposition of immuno complexes has been suggested as a mechanism of glomerular injury in AKI induced by dengue [ 28 ].…”
Section: Discussionmentioning
confidence: 99%